Laboratory Tests for Diagnosis of Alcoholic Liver Disease - Peta, Valentina; Elaribi, Djamel; Abenavoli, Ludovico (Reviews on Recent Clinical Trials, 2016)
Alcohol is considered one of the most common hepatotoxin, and chronic alcoholic liver disease is affecting millions of subjects worldwide. The three most frequently manifestations of alcoholic liver disease are steatosis, acute alcoholic hepatitis and liver cirrhosis. The diagnosis of Alcoholic Liver Diseases (ALD) is made by clinical and laboratory analysis. Actually do not exist a single laboratory test able to confirm the diagnosis of ALD, but in the last years several serum markers and laboratory abnormalities have been discovered in these patients. In particular the combination of tests and markers can increase the diagnostic accuracy, for this reason the last studies are focusing on the development of serum biomarkers panel able to diagnose alcohol-related liver damage.
Keywords: Alcoholic liver disease